Microstructure, Hardness and Tribological Characteristics of High-Entropy Coating Obtained by Detonation Spraying - Zhuldyz Sagdoldina; Laila Sulyubayeva; Dastan Buitkenov; Yedilzhan Kambarov (Crystals, 2025)
In this study, powders based on a high-entropy AlCoCrFeNi alloy obtained by mechanical alloying were successfully applied to a 316L stainless steel substrate by detonation spraying under various conditions. Their microstructural features, phase composition, hardness, and wear resistance were studied. A comparative analysis between the initial powder and the coatings was performed, including phase transformation modeling using Thermo-Calc under non-equilibrium conditions. The results showed that the phase composition of the powder and coatings includes body-centered cubic lattice (BCC), its ordered modification (B2), and face-centered cubic lattice FCC phases, which is consistent with the predictions of the Scheil solidification model, describing the process of non-equilibrium solidification, assuming no diffusion in the solid phase and complete mixing in the liquid phase. Rapid solidification and high-speed impact deformation of the powder led to significant grain refinement in the detonation spraying coating, which ultimately improved the mechanical properties at the micro level. The data obtained demonstrate the high efficiency of the AlCoCrFeNi coating applied by detonation spraying and confirm its potential for use in conditions of increased wear and mechanical stress. AlCoCrFeNi coatings may be promising for use as structural materials in the future.